RACISM TOWARDS AFRICAN AMERICAN COMMUNITY AS REFLECTED IN MAYA ANGELOU’S I KNOW WHY THE CAGED BIRD SINGS: BLACK AESTHETIC CRITICISM - Gisa Maya Saputri (Universitas Gadjah Mada, 2021)
The study of the African American community always circulates among the issues of race, racism, discrimination, slavery, and oppression. All these issues become the grand themes of African American literature. These literary works could be studied and covered under the scope of Black Aesthetic criticism. One of the prominent works of African American literature is an autobiography of Maya Angelou entitled I Know Why the Caged Bird Sings (1969). This autobiography portrays Angelou’s childhood experiences which brings up the issues of race, racism, and oppression. This paper aims to analyze the kinds of racism experienced by the African American community and their struggle against it as depicted in the book. To provide a thorough discussion of the matter, critical race theory was employed as the method of analysis. The result is drawn based on the basic tenets of critical race theory proposed by Richard Delgado and Jean Stefancic (2001); everyday racism, interest convergence, the social construction of race, differential realization, intersectionality, and voice of Color. The findings show the struggle of African American community against racism which are expressed through the act of ignorance, promoting intelligence, communal efforts, resistance, promoting social movement, and stepping forward to voice their experience through African American literature.